Analisis Penggunaan Obat di RSUD Kota Yogyakarta Berdasarkan Indikator WHO - Inaratul Rizkhy Hanifah (Fakultas Farmasi Universitas Setia Budi, 2011)
Prescribing the rational drugs is the main orientation of the health care activity that should be increase in quality. The research objective’s are to analyze of drug use of patient in RSUD Kota Hospital in the march 2010 period based on WHO’s core indicator and complementary indicator. This research is non-experimental, descriptive design, and prospective data collective. The results obtained in RSUD Kota hospital are appropriate with standards WHO percentage of encounter with an antibiotic prescribed 21.89%, and injection 0%, while inappropriate the standards is the average drug items used per encounter 2.33, percentage of drugs prescribed by generic name 29.29% and percentage of drugs prescribed from formulary 83.84%. Patient care indicators, the average dispensing time was 17.59 minutes (non-compounded) and 25.67 (compounded), where 94.29% of drugs are dispensed and no one adequately labeled. Health facility indicators, there was formulary availability, and availability of key drugs 100%. WHO complementary indicators in RSUD Kota Hospital that average drug cost per encounter 50914.60 IDR, with 28.95% cost spent on antibiotics and injections of 0%.